Assimilate Hugging Face. (Pragmatic AI Solutions, 2022)
Assimilate Hugging Face Learn Hugging Face weekly by example This video course will show you how to build real-world applications with Hugging Face. Topics Covered Include: 1.0 Assimilate Hugging Face EP1 build cli tool summarize codespaces 2.0 Assimilate Hugging Face EP2 Building CLI Summarizer gradio webapp Learning Objectives Build a CLI tool that invokes models with Hugging Face Use Github Codespaces to code alongside Github Copilot. Additional Popular Resources 52 Weeks of AWS-The Complete Series Pytest Master Class AWS Solutions Architect Professional Course Github Actions and GitOps in One Hour Video Course Jenkins CI/CD and Github in One Hour Video Course AWS Certified Cloud Practitioner Video Course Advanced Testing with Pytest Video Course AWS Solutions Architect Certification In ONE HOUR Python for DevOps Master Class 2022: CI/CD, Github Actions, Containers, and Microservices MLOPs Foundations: Chapter 2 Walkthrough of Practical MLOps Learn Docker containers in One Hour Video Course Introduction to MLOps Walkthrough AZ-900 (Azure Fundamentals) Quick reference guide 52 Weeks of AWS Episode 8: Infrastructure as Code with CDK and AWS Lambda Learn GCP Cloud Functions in One Hour Video Course Python Devops in TWO HOURS! MLOps Platforms From Zero: DatMLOps Platforms From Zero: Databricks, MLFlow/MLRun/SKLearn AWS Machine Learning Certification In ONE HOUR Fast, documented Machine Learning APIs with FastAPI Zero to One: AWS Lambda with SAM and Python in One Hour AWS Storage Solutions 2022: EBS/S3/EFS/Glacier Python Bootcamp for Data Testing In Python book Minimal Python book Practical MLOps book Python for DevOps-Playlist.